REVIVAL OF TODA EMBROIDERY-NEEDLECRAFT OF NILGIRIS - Garima Sharma; Simmi Bhagat (Jurnal Sosioteknologi, 2018)
The Toda are an ancient pastoral people who live in the cool uplands of the Nilgiri Mountains of Tamil Nadu, India. Toda women do an aesthetically great   and intricate form of embroidery and it holds a cultural uniqueness for the Toda community. This distinct style of embroidery is locally known as "Pugur" or "Pukhoor". In the current study an effort has been made to preserve and revive this craft with the focus on documentation, creating general awareness and capacity building of the artisans. Interventions were planned for the revival and preservation of this traditional craft and community. A video on the tribal craft has been made to for introducing it to the masses for increasing awareness about the craft through social media and video screening sessions. A motif/design catalog was also prepared for use by artisans and designers. Also, it was found that design education for artisans at the local level is the most effective model because it focuses on all-round education for the artisan. Thus, a clothing line was designed for men, women, and kids and design layouts were provided to the artisans for understanding placement of embroidery pattern.